Molecular, Physico-Chemical, and Sensory Characterization of the Traditional Spanish Apple Variety “Pero de Cehegín” - Ramón Martínez; Pilar Legua; Francisca Hernández; Ángel Carbonell-Barrachina; Yolanda Gogorcena; Juan J. Martínez-Nicolás; Pablo Melgarejo (Agronomy, 2020)
The “Pero de Cehegín” is an ancient local variety of apple grown in Murcia (Spain). In this study, microsatellites markers showed evidence of a unique profile that has never been reported before in other Spanish apple germplasm collections. Five “Pero de Cehegín” clones were evaluated and compared with two commercial apple varieties, “Fuji” and “Golden Delicious”, to assess its marketing potential. For this, the physical (weight, height, and width of the fruit, moisture content, firmness, and color of the fruit, among others), and chemical (total soluble solids, total acidity, and maturity index) properties of the fruits were evaluated. In addition, the content of bioactive compounds such as total polyphenol content, total antioxidant activity using the ABTS+, DPPH•, and FRAP methods, and the sugar profile were analyzed, and their sensory profile was also evaluated. Physico-chemical differences were found within the “Pero de Cehegín” clones and between the commercial varieties. “Pero de Cehegín” had a high firmness, high total soluble solids, very low total acidity, high FRAP antioxidant capacity, and more sucrose content in comparison with “Fuji” and “Golden Delicious”. These distinctive characteristics and the good appearance of the fruit make this variety a marketable product that will increase the offering of traditional, local, but underutilized fruit varieties.